2016
DOI: 10.1016/j.jfluchem.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Modified coin cells to evaluate the electrochemical properties of solid-state fluoride-ion batteries at 150 °C

Abstract: . Modified coin cells to evaluate the electrochemical properties of solid-state fluoride-ion batteries at 150°C. Journal of Fluorine Chemistry, Elsevier, 2016, 191, pp.23 -28. 10 AbstractIn the scope of developing new chemistries for electrochemical energy systems, rechargeable solid-state fluoride-ion batteries are attractive devices owing to their high theoretical energy density. State of the art of fluoride ion conductors require the use of high temperature electrochemical cells to overcome the low ionic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Further, coin cell based systems were proposed by Grenier et al, where a high temperature stable epoxy resin can be used for sealing, facilitating improved longer-term operability. 31 There also exist some reports 32,33 on FIBs, which are based on liquid electrolytes, which can then be investigated in the most common Swagelok-type setup. For instance, Davis et al reported 33 on standard three electrode systems for FIBs based on a liquid electrolyte.…”
Section: Design Of All-solid-state Cells Used For Fibsmentioning
confidence: 99%
“…Further, coin cell based systems were proposed by Grenier et al, where a high temperature stable epoxy resin can be used for sealing, facilitating improved longer-term operability. 31 There also exist some reports 32,33 on FIBs, which are based on liquid electrolytes, which can then be investigated in the most common Swagelok-type setup. For instance, Davis et al reported 33 on standard three electrode systems for FIBs based on a liquid electrolyte.…”
Section: Design Of All-solid-state Cells Used For Fibsmentioning
confidence: 99%
“…Apart from some limited reports on primary batteries based on fluoride ions in the 1970s 11,12 , the first report on electrochemical rechargeable FIBs was proposed at 2011 by Fichtner et al 13 , based on an all-solid-state battery with La 0.9 Ba 0.1 F 2.9 as the solid electrolyte and conversion-based metal fluorides as active electrodes (e.g., CuF 2 , BiF 3 , and SnF 2 as the active cathode materials). Since then, the efforts on investigating such systems were further increased, addressing the development of solid [14][15][16][17][18] and liquid 19,20 electrolytes and improved cell designs 21,22 as well as the screening of conversion-based electrodes [23][24][25][26] .…”
mentioning
confidence: 99%
“…Recently, a variety of secondary batteries have been developed . Our group selected and developed fluoride shuttle battery (FSB) with liquid‐electrolyte .…”
Section: Figurementioning
confidence: 99%